Interpretasi Konsep Perbudakan dalam Al-Qur’an (Studi Analisis Tematik Al-Farmawi Terhadap Frasa Milkul Yamin) - Handayani, Ikrimah Retno; Muhammad, hafid nur; Arifin, Ali Zainal; Zainab (Ulumul Qur'an: Jurnal Kajian Ilmu Al-Qur'an dan Tafsir, 2024)
This study aims to examine the concept of milkul yamin in the Qur'an and its relevance to modern times. Using Abdul Hayy al-Farmawi's thematic method theory, this research is library research with a qualitative approach. Primary data is obtained from the Qur'an and books of tafsir, while secondary data is from supporting books and previous articles. The results show that the concept of milkul yamin is not only related to slaves or sexual problems but also concerns social and humanitarian problems. The Qur'an wants the gradual abolition of the slavery system by providing guidelines for fakku-raqabah. Although the locus of slavery is no longer relevant in modern times, the essence of the Qur'an as a guideline still applies, especially in upholding human rights and overcoming various forms of modern slavery such as labour exploitation, human trafficking, and sexual exploitation.